Study on the propagation law of hydraulic fractures in heterogeneous permeability reservoirs. - Linhao Zou; Yinao Su; Xingsheng Xu; Wei Li; Huan Zhao; Mingxiu Zhang; Shengjie Jiao (PLoS ONE)
The development of unconventional oil and gas resources is increasingly shifting toward heterogeneous reservoirs with complex permeability distributions, making the effective control of hydraulic fracture propagation patterns critical for optimizing production. To this end, this study establishes a 3D multilayered heterogeneous reservoir model using the finite element method to analyze fracture mechanisms. The impacts of permeability heterogeneous, injection rate, and fracturing fluid viscosity on fracture morphology are systematically investigated, and the elasticity coefficient method was used to evaluate the influence weights of each parameter.The main conclusions are as follows: (1) Permeability distribution is the core factor controlling the fracture propagation direction, with HPL dominating the extension path while MPL and LPL show limited efficiency. (2) An increase in the number of permeability layers inhibits the overall expansion of cracks, and the shape of the cracks gradually changes to rectangular. (3) Higher injection rates significantly expand fracture area, whereas fracturing fluid viscosity ≥50 mPa·s stabilizes fracture morphology. (4) The elastic coefficient method identifies injection rate, permeability heterogeneous, and fracturing fluid viscosity as the key control parameters in order. This work provides theoretical guidance for optimizing hydraulic fracturing parameters in complex geological settings.